Cross-cultural adaptation and validation of Leicester Cough Questionnaire in sarcoidosis: the persian version - Rahdar, Mohammad; Kiani, Arda; Noorali, Sima; Bakhshandeh, Arezoo; Hosseini-Baharanchi, Fatemeh Sadat; Shafaghi, Shadi; Abedini, Atefeh; kharazmi, Amir Behnam (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Cough is a common symptom among patients with sarcoidosis, and the Leicester Cough Questionnaire, a cough-specific quality-of-life measure, evaluates the impact of cough across physical, psychological, and social domains in patients with chronic cough. The aim of this study was cross-cultural adaptation and validation of Persian version of Leicester Cough Questionnaire (LCQ) in pulmonary sarcoidosis in Iran. Methods: Psychometric analyses included translation and back translation of the questionnaire, face validity, content validity, construct validity, criterion-related validity, internal consistency, and test –retest reliability were performed. Results: Twenty-five participants demonstrated no major language barriers or difficulties in completing the questionnaire and adequate face validity of ≥1.5. Twelve experts confirmed the content validity was good (CVR˃0.56, I-CVI≤0.79, S-CVI/Ave˃0.80). Totally, 190 patients were included in the study. The Pearson's coefficients and their significance's (P